2016
DOI: 10.3389/fphar.2016.00426
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Near Infrared Dyes as Markers of P-Glycoprotein Activity in Tumors

Abstract: Aim: The multidrug resistance protein 1 (MDR1; P-glycoprotein) has been associated with efflux of chemotherapeutic agents from tumor cells and with poor patient prognosis. This study evaluated the feasibility of non-invasive, non-radioactive near infrared (NIR) imaging methodology for detection of MDR1 functional activity in tumors.Methods: Initial accumulation assays were conducted in MDR1-overexpressing MDCK cells (MDCK-MDR1) and control MDCK cells (MDCK-CT) using the NIR dyes indocyanine green (ICG), IR-783, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…We chose other ASBT inhibitors (Nifedipine and cyclosporine A) and substrate (taurocholate and deoxycholate) for the validation. Nifedipine has been reported as an ASBT inhibitor; however, the ICG intensity increased on pretreatment with Nifedipine (Figure 7d,f), because Nifedipine is also an MDR1 inhibitor and the ICG efflux transporter [13,29]. The half maximal effective concentration (EC50) value of ICG for MDR1 is 15 ± 1.1 µM in Madin-Darby canine kidney (MDCK) cells with MDR1 overexpression [30].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We chose other ASBT inhibitors (Nifedipine and cyclosporine A) and substrate (taurocholate and deoxycholate) for the validation. Nifedipine has been reported as an ASBT inhibitor; however, the ICG intensity increased on pretreatment with Nifedipine (Figure 7d,f), because Nifedipine is also an MDR1 inhibitor and the ICG efflux transporter [13,29]. The half maximal effective concentration (EC50) value of ICG for MDR1 is 15 ± 1.1 µM in Madin-Darby canine kidney (MDCK) cells with MDR1 overexpression [30].…”
Section: Discussionmentioning
confidence: 98%
“…Indocyanine green (ICG), a Food and Drug Administration (FDA) approved drug (dye) for liver function testing and tumor detection, is a near-infrared fluorophore with better penetration and lower autofluorescent background compared with traditional fluorescent proteins, such as green fluorescent protein (GFP) and red fluorescent protein [7][8][9][10][11]. The influx and efflux of ICG occur through NTCP and OATP1B3 and multidrug resistance p-glycoprotein 3 (MDR3) and multidrug resistance p-glycoprotein 1 (MDR1), respectively [12][13][14]. In our previous study, we demonstrated the use of NTCP and OATP1B3 as reporter genes combined with ICG for in vivo tumor cell tracking [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescent substrates of the transporter have been commonly used to image and assess its efflux function in pre-clinical settings. Indocyanine green (ICG) was the first FDA-approved dye used for fluorescence imaging of ABCB1 [ 5 , 6 ]. However, a statistically non-significant 1.7-fold difference in ICG fluorescence was observed between ABCB1-overexpressing tumors and normal tissues in mouse xenografts [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indocyanine green (ICG) was the first FDA-approved dye used for fluorescence imaging of ABCB1 [ 5 , 6 ]. However, a statistically non-significant 1.7-fold difference in ICG fluorescence was observed between ABCB1-overexpressing tumors and normal tissues in mouse xenografts [ 6 ]. This suggests there is a need for enhanced fluorescence selectivity to label ABCB1 in diseased tissues.…”
Section: Introductionmentioning
confidence: 99%